Using online corrective feedback in the editing stage of academic writing among ESL undergraduates / Cecilia Bai Rajendran... [et al.] - Bai Rajendran, Cecilia; Soo, Carolyn Kum Yoke; Sain, Noridah; Kamaludin, Puteri Nur Hidayah; Md Nawi, Sofwah; Mohd Yusof, Suhaili (2012)
It cannot be denied that the internet is an indispensable medium in the teaching and learning environment. As such, the aim of this study is to investigate the effectiveness of using online corrective feedback for academic writing classrooms compared to conventional corrective feedback methods. It would be interesting however, to find out if a more innovative form of corrective feedback can be introduced into the ESL writing classroom by means of interactive computer tools namely Microsoft Word Processor. In order to do this, an experimental design has been selected to compare a control and an experimental group of undergraduates pursuing the English for Academic Purposes course. A survey would also be conducted to determine how feasible the use of online corrective feedback is when used to help students improve from the first draft to second draft stage which involves editing in the process writing approach for academic writing classrooms. Statistical SPSS tools would be used to compare the conventional and experimental methods for analysis. Basically, the online corrective feedback should save time and cost, besides improving writing skills among ESL undergraduates, besides providing an enriching experience for both instructors and learners for effective teaching and learning in writing classrooms. The results of the study should help in determining this method's feasibility for application to the academic writing classroom.